Observing crossroads to corporate climate action through insights from Japanese and German climate activists - Solange Annaik Commelin (npj Climate Action)
Abstract This study uses interviews and social media data from Japanese and German climate activists to investigate how interactions between their groups and corporations foster climate action. It sheds light on this underexplored relationship through valuable insights into the barriers delaying and pathways supporting corporate climate action. The findings reveal how activists’ communicated perceptions are linked to both movement activity, such as the use of specific protest forms, and individual actions, like refusing to work for certain companies. The subtle variations in results between Japan and Germany underscore the importance of researching climate movements from a multinational perspective. Overall, the study provides new insights on these influential actors in the context of the climate crisis, while also emphasizing the need for more comprehensive and inclusive evaluations of the complex activist–corporate relationship.